Persuasion knowledge transfer: A conceptual model - Saidin, Aeni Zuhana; Macaulay, Catriona; Hine, Nick (2012)
Researchersare fully aware that the transfer of specialised knowledge to designer is important.This demand is especially high within the growing domain of persuasive technology that requires designers to grasp persuasion knowledge in order to design product, application or services that able to change peoples’ attitude and behaviour. Therefore, this study aims to explore ways on how persuasion knowledge can be transferred and used during the design ideation stage.The literature analysis method was used to analyse the important persuasion elements involved in persuasive design.It become the basis of the conceptual model of persuasion knowledge transfer in inspiring the persuasive design ideas during the design process.